Acylated flavonol glycosides and terpenoids from the leaves of Alibertia sessilis - Olea, RSG; Roque, N. F.; Bolzani, Vanderlan da Silva [UNESP] (Soc Brasileira Quimica, 1997)
Two novel acylated flavonol glycosides, along with iridoids, triterpenes, steroids and alpha-tocopherolquinone, were isolated from the leaves of Alibertia sessilis (Rubiaceae). The determination of the structures of the new compounds was based mainly on H-1- and C-13-NMR.
Keywords: Alibertia sessilis; Rubiaceae; acylated flavonol glycosides; iridoids; terpenoids; alpha-tocopherolquinone